PM2.5-bound polycyclic aromatic hydrocarbons and elements in different environments in southern Taiwan and their potential toxic effects on Caenorhabditis elegans models - Lee, Jia De; Lu, Jian He; Chang, Yi Kuo; Lin, Sheng Lun; Jiang, Jheng Jie; Huang, Chien Er; Tsai, Jen Hsiung; Wan Mansor, Wan Nurdiyana; Hsieh, Ping Heng; Juan, Tai Jui; Chao, How Ran; Jalaludin, Juliana (Springer International Publishing, 2025)
Fine particulate matter (PM2.5) has been demonstrated to disrupt developmental, neurological, and reproductive functions in animal models including Caenorhabditis elegans (C. elegans). In the present study, PM2.5-bound polycyclic aromatic hydrocarbons (PAHs) and elements were studied in urban, traffic-related air pollution (TRAP), and industrial areas to examine whether PM2.5-bound PAHs or elements caused toxic effects in C. elegans. PM2.5 collected from these areas (25.9, 41.7, and 28.9 μg m−3 in urban, TRAP, and industrial areas, respectively) caused significant toxic effects on development (body growth, 85.8%–95.9% reduction), reproduction (brood size, 52.5%–85.8% reduction), and neurology (locomotion, 49.7%–84.3% and 72.3%–94.5% declines in head thrashing and body bending frequencies, respectively), along with changes in the expression of genes regulating antioxidant mechanisms. Despite its lowest PM2.5 concentration, the industrial site induced stronger reproductive and locomotor toxicity, accompanied by heightened antioxidant gene expression. To further elucidate the role of PM2.5 composition in these effects, concentrations of PAHs, PAH-BaPeq, and elements were quantified in the nematode exposure models. Our results showed that PM2.5-bound Σ16PAH (0.501–0.658 ng m⁻3) and PAH-BaPeq (0.0497–0.0698 ng BaPeq m⁻3) levels did not differ significantly among the three areas; however, toxic metal concentrations—particularly lead and copper—were substantially higher in the industrial samples than in those from the urban and TRAP environments. The reproductive and locomotor toxicity, along with increased superoxide dismutase (SOD)-related reactive oxygen species (ROS) production observed in nematodes exposed to low-dose industrial PM2.5, is likely more strongly associated with elevated levels of PM2.5-bound toxic metals than with exposures from urban or TRAP regions. Compared with PM2.5-bound PAHs, PM2.5-bound lead or copper might contribute more substantially in triggering the toxic responses of PM2.5 in nematodes, particularly on oxidative stress, reproduction, and locomotion, according to the findings of the current study.